Relación entre clima organizacional y síndrome de burnout en el servicio de emergencia de un hospital Categoría III-2. Lima, Perú 2015 - Solís Chuquiyauri, Zenaida (2016)
Objective: To determine the relationship between organizational climate and Burnout Syndrome among nursing professionals of the Emergency Service in a Hospital Category III-2. Material and methods: quantitative, prospective, correlational cross-sectional study. The sample consisted of 43 nurses, using a non-probability sampling for convenience. For analysis and study of the variables, Rensis Likert scale and Maslach Burnout Inventory were used. Results: The organizational climate was average level (81.4%) followed by a high level (18.6%) and the Burnout Syndrome corresponds to low level (86%) and medium (14%) level. The relationship between organizational climate and Burnout Syndrome was low (rho = -0.11). Conclusions: In the Emergency Service, the level of organizational climate was fairly favorable with absence of Burnout Syndrome among nursing professionals. There is not significant relationship between the two variables.